Improving the Performance of Transparent Conducting Electrodes Based on Cu Nanowires - Mardiansyah, Dedi; Usna, Sri Rahayu Alfitri; Nafisah, Suratun; Harsojo, Harsojo; Hatika, Rindi Genesa (Universitas Gadjah Mada, 2024)
The fabrication of transparent conducting electrodes (TCEs) is dominated by indium tin oxide (ITO). Some efforts are being made to find alternative materials as a substitute for ITO. Cu nanowire (CuNWs) is an equivalent candidate as a replacement for ITO but has a weakness that is easily oxidized. In this contribution, we report an increase in the performance of CuNWs, which can reduce the effect of oxidation. In this study, we provide a coating of CuNWs using PVP, PVA, and silver nanoparticles (AgNPs). The morphology, formation structure, and conductivity of CuNWs have been investigated by scanning electron microscope (SEM), X-ray diffraction (XRD), and IV meter. The average length and diameter of the CuNWs were 5.5 μm and 120 nm, respectively. The transparent conducting has a stable conductivity after coating with PVP, PVA and AgNPs. The application of transparent conducting electrodes are sensors, electronic devices, solar cells, and organic light-emitting diodes (OLEDs).